GE_GERICHTE A/4473/2015 vom 17. März 2016 - GE Cour de justice (2016)
Application de l'art. 97 al. 2 LP en cas de séquestre. Intérêt du créancier pour former plainte. | LP.17.1; LP.97.2; LP.274.1; LP.275